"How obsessive are dentists?"––A personality styles & disorder inventory based prospective, controlled study. (September 2022) - Wolf, Thomas Gerhard; Speyer, Valerie Fabienne Sonja; Peter, Burkhard
Abstract: Objectives: The aim of this study was to examine the typical personality traits of dentists and to discuss critically their influence on the necessary characteristics for a good dentist-patient relationship. Methods: Two groups were invited via e-mail to participate the study in 2015–2020. One group consisted of German dentists (DENT N = 580). The other group was formed by German speaking psychotherapists from Germany, Austria and Switzerland (DACH N = 1.027). The Personality Styles and Disorder Inventory was used in its short form (PSDI-S) via online survey. The normalization sample (NORM N = 3.392) of the PSDI-S was used to compare the results with a normative sample. Results: Dentists differed in 10 out of 14 personality styles from the normalization sample (NORM), and in 13 out of 14 personality styles compared with the psychotherapists (DACH). Female dentists differed in 7 out of 14 personality styles to their male colleagues. Conclusions: The most significant differences in personality styles were willful (PN), spontaneous (BL), reserved (SZ), ambitious (NA), optimistic (RH) and conscientious (ZW), which seem to be necessary for a good dentist-patient relationship and dental procedures. The expression of personality styles is most likely to influence the choice, delivery and cost as well as patient perception of treatment. Clinical significance: Dentist's personality has an important impact on the interpersonal, which influences the dentist-patient relationship and its therapeutic outcome.